Determinants of Stress Levels in Pharmacy Installation Officers at Tgk Regional General Hospital. Abdullah Syafii Year 2023 - Riska Wardani; Donal Nababan; Janno Sinaga (SEAN Institute, 2023)
Stress is often associated with accumulated levels of fatigue which can be a factor influencing stress, fatigue not only affects the health and welfare of officers but also endangers the performance of officers, resulting in an increased risk of patient safety. Empirical evidence suggests that accumulated fatigue can accelerate thrombotic reactions and even cause sudden cardiac arrest. The medical and health care industry is particularly vulnerable to the accumulation of work-related fatigue due to its specific nature, such as workload, fatigue, interactions with superiors, interactions with co-workers and interactions with patients which are related to stress levels. This study used an analytical research method, which is a research design that aims to determine the factors associated with stress levels in IFRS officers at Tgk Hospital. Abdullah Syafii. This research was conducted on 46 pharmaceutical installation staff respondents consisting of 27 women and 19 men. In this study, data analysis was carried out using a questionnaire and the data would be analyzed using univariate, bivariate, and multivariate analysis techniques, presenting data and drawing conclusions. The results of the analysis show that the most dominant factor influencing the stress level of Pharmacy Installation Officers in Hospitals is interaction with colleagues and interactions with superiors. For this reason, it is hoped that the hospital will have problems interacting with colleagues and interactions with superiors to find ways to make good relations happen for all so that there is no stress on the installation staff even though the stress that occurs is only at a mild stress level. This research was conducted on 46 pharmaceutical installation staff respondents consisting of 27 women and 19 men. In this study, data analysis was carried out using a questionnaire and the data would be analyzed using univariate, bivariate, and multivariate analysis techniques, presenting data and drawing conclusions. The results of the analysis show that the most dominant factor influencing the stress level of Pharmacy Installation Officers in Hospitals is interaction with colleagues and interactions with superiors. For this reason, it is hoped that the hospital will have problems interacting with colleagues and interactions with superiors to find ways to make good relations happen for all so that there is no stress on the installation staff even though the stress that occurs is only at a mild stress level. This research was conducted on 46 pharmaceutical installation staff respondents consisting of 27 women and 19 men. In this study, data analysis was carried out using a questionnaire and the data would be analyzed using univariate, bivariate, and multivariate analysis techniques, presenting data and drawing conclusions. The results of the analysis show that the most dominant factor influencing the stress level of Pharmacy Installation Officers in Hospitals is interaction with colleagues and interactions with superiors. For this reason, it is hoped that the hospital will have problems interacting with colleagues and interactions with superiors to find ways to make good relations happen for all so that there is no stress on the installation staff even though the stress that occurs is only at a mild stress level.